2002
DOI: 10.1016/s0272-6963(02)00087-6
|View full text |Cite
|
Sign up to set email alerts
|

Six Sigma: a goal‐theoretic perspective

Abstract: Six Sigma is a phenomenon that is gaining wide acceptance in industry, but lacks a theoretical underpinning and a basis for research other than "best practice" studies. Rigorous academic research of Six Sigma requires the formulation and identification of useful theories related to the phenomenon. Accordingly, this paper develops an understanding of the Six Sigma phenomena from a goal theoretic perspective. After reviewing the goal theory literature, these concepts, when applied to Six Sigma, suggest some prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
607
0
42

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(659 citation statements)
references
References 38 publications
10
607
0
42
Order By: Relevance
“…In addition, findings indicate that on-field performance has a significant impact on factors including service quality in sport events and that the unsuccessful management of players as suppliers can make or break a professional sports teams' profits. Further research opportunities therefore include the application of operations management to the analysis and improvement of on-field performance using Quality Function Deployment (Mehrjerdi, 2010), Six Sigma (Linderman et al, 2003) or by utilizing traditional SCM practices in managing a supply of talent. It should be noted that as the opportunities demonstrated in this paper are based on the findings of the study only, the proposed research agenda is not intended to be exhaustive and merely provides a starting point for further work in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, findings indicate that on-field performance has a significant impact on factors including service quality in sport events and that the unsuccessful management of players as suppliers can make or break a professional sports teams' profits. Further research opportunities therefore include the application of operations management to the analysis and improvement of on-field performance using Quality Function Deployment (Mehrjerdi, 2010), Six Sigma (Linderman et al, 2003) or by utilizing traditional SCM practices in managing a supply of talent. It should be noted that as the opportunities demonstrated in this paper are based on the findings of the study only, the proposed research agenda is not intended to be exhaustive and merely provides a starting point for further work in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Sports equipment manufacturing and retail are excluded from the scope of this paper as they are seen as a separate industry related more closely to retail than to sport. This paper does not consider the potential application of OM to on-field sport performance, however this context is recognized as another possible outlet for research as certain tools such as Statistical Process Control (SPC) and Six Sigma have the potential to be used in improving athlete performance (Antony, 2000, Linderman et al, 2003.…”
mentioning
confidence: 99%
“…It is based on statistical and scientific methods for drastic reductions in the default rates defined by the client (Linderman et al, 2003;Dora & Gellynck, 2015). The Six Sigma methodology was created by Motorola in the 1980s to face the Japanese threat in the electronics industry (Banuelas et al, 2005).…”
Section: Six Sigma Methodologymentioning
confidence: 99%
“…In the last two decades, it is observed that global companies have maximised business benefits and gained competitive advantage by implementing Six Sigma (Yang andHsieh, 2009, Su andChou, 2008,). Six Sigma has been defined as a systematic and organised method of improving process and development of new products and services that rely on statistical and scientific methods to reduce customer-defined defect rates to a very high level (Linderman et al, 2003). A Six Sigma process approaches 'zero defects', which means only 3.4 Defects Per Million Opportunities (DPMO) might occur.…”
Section: Introductionmentioning
confidence: 99%